PEMBEBASAN PEREMPUAN DALAM NOVEL BANĀT AL-RIYĀḌ KARYA RAJA’ ABD ALLĀH AL-ṢĀNI’ - M. Faisol; Ahmad Kholil (Adabiyyāt: Jurnal Bahasa dan Sastra, 2018)
In the midst of dominant patriarchal culture ini Saudi Arabia, Banāt al-Riyāḍ novel by Raja’ ‘Abd Allāh al-Ṣāni’ is present as an effort to liberate women from the dominant patriarchal confines. As woman author, Raja’ ‘Abd Allāh al-Ṣāni’ made criticism and resistance in her work as an effort to liberate women. Through women as writer approach, this paper aims to reveal efforts to fight for women’s rights and liberation from the dominance of tyrannical hegemonic masculinity in the Saudi Arabian setting. The results of the analysis show that female leaders emerged in the movement of awareness when their rights were taken. They made efforts to free themselves by suing the confines of tradition and patriarchal religious construction. Liberating women from the oppressive male domination by the leaders is the attempt to free women, both in the domestic and public shpheres. Novel Banāt al-Riyāḍ is an author’s strategy in its efforts to fight for the rights of Saudi Arabian women and to free them from patriarchal confines.